The Evolution of Literature. : Legacies of Darwin in European Cultures. - Edited by Nicholas Saul and Simon J. James (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2011)
Daniel Dennett famously claimed for Darwinian theory the status of universal solvent: the totalising theory of theories, even of theories of literature. Yet only a few writers and critics have followed his view. This volume asks why. It examines both evolution in literature, and the evolution of literature. It looks at literary representations of Darwinism both historically and synchronically, at how a theory of literature might be derived from evolutionary theory, and indeed how evolution as a process might be regarded as itself aesthetic. It complements these theoretical and historical dimensions of enquiry with the comparative dimension. It asks in short: What have been the representations of Darwinian evolutionary theory in literature since the late nineteenth century? What are the leading paradigms in theory and in literature for renovating the evolutionary model? What were, and are, the differences in British, French, German paradigms of literary Darwinian reception? How, if at all, did Darwinian modes of thought hybridise across national borders? Last, but not least: What is the future of the Darwinian mode?